THE EFFECT OF DISCOVERY LEARNING MODEL ON STUDENTS' MATHEMATICAL COMMUNICATION SKILLS: META ANALYSIS - Ulhanan, Dhiya; Hasanuddin, Hasanuddin (Guruku: Jurnal Pendidikan Profesi Guru, 2025)
One important aspect in improving students' mathematical communication ability is the use of the right learning model, one of which is through the Discovery Learning (DL) model. The purpose of writing this article is to find out how much influence the DL model has on student performance. This study is important because it provides a thorough review of the effectiveness of the DL model based on findings from various previous studies. The method used is SLR with meta-analysis guidelines for ten articles, using Cohen's formula to calculate the effect size value. The results showed one article in the medium category (0.47) and nine others in the very large category (1.046-7.27). This finding shows that Discovery Learning is effective in improving mathematical communication skills. This article contributes to strengthening the empirical foundation and provides recommendations for the application of this model in mathematics learning practices.